Christianity and radical democracy in the Philippines : building a church of the poor - Moxham, Christopher (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book analyses faith-based development action in the Philippines by studying Catholic social movements and development studies in Southeast Asia. By drawing upon primary, qualitative data, this book examines cultural production and community resilience amid poverty and structural restraints. It also interrogates the discourse of Basic Ecclesial Communities, the smallest organisational unit of the Philippine Catholic Church, to better understand the strengths and weaknesses of the social movement. The author shows that the dream of local economic development and empowerment requires help from the Catholic hierarchy, particularly the organizational and leadership resources at the diocese level. This book is a unique contribution in opening up interdisciplinary approaches to religion, faith and social development. It will be of interest to researchers on Asian Studies, especially Southeast Asian Studies, Development Studies, the Anthropology of Development, Social Movements, and the Anthropology of Christianity, Missiology and Religious Studies"--
Basic Ecclesial Communities in the Philippines : Philosophical Roots and a Place in Critical Development Studies -- Republika NG Pilipinas and The Island of Negros -- Development in the Diocese of San Carlos -- Basic Ecclesial Communities in San Carlos: Place-Making, Social Capital, and the Structures that Limited Development -- BECs, the Diocese, the Discourse, and Development : Potentials, Limits, Recommendations.
Keywords: Catholic Church -- Philippines; Basic Christian communities -- Philippines; Community development -- Philippines; Community development -- Religious aspects -- Catholic Church; Christian communities -- Catholic Church; Philippines -- Religious life and customs; SOCIAL SCIENCE / Ethnic Studies / General